Adolescents Health Indicators in the Occupied Palestine Territory: Focus on Sexual and Reproductive Health - Niveen M. E. Abu-Rmeileh (3663745) (2025)
Adolescents face many barriers to health services, especially in humanitarian crises. Health indicators and their sources collected during humanitarian crises will help identify gaps in the data to inform policy and practice. This study aims to determine the available indicators of adolescents’ health, and reproductive health, in humanitarian crises. Secondary data analysis. An extensive document search was conducted to collect adolescent health indicators in Palestine. Our search included surveys, reports, assessments done by humanitarian organizations, and peer-reviewed journal articles. Population health surveys were the primary source for adolescent health indicators, specifically the Demographic Health Survey and the Multiple Indicator Cluster Surveys. Two-thirds of the indicators covered the childbearing process (antenatal care, postnatal care, and delivery), 19% were about the knowledge of HIV/AIDs, and 16% were about early marriage. Almost all indicators targeted females, and only 9% targeted both males and females. The Reproductive health indicators mainly were married females aged (15–19) and, nothing was reported for those between 10 and 14 years. Although the available indicators identified are of good quality, they are missing adolescent males and younger groups. Reliable data-based indicators are needed, which can be achieved by creating a national registry for adolescent health indicators or implementing longitudinal surveys to track trends over time. Other Information Published in: Child Indicators Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12187-025-10230-0